2018
DOI: 10.1007/s00296-018-4150-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation, treatment and outcome of Takayasu’s arteritis in southern Chinese: a multicenter retrospective study

Abstract: To study the clinical presentation, treatment and outcome of southern Chinese patients with Takayasu's arteritis (TA). This is a retrospective chart review study of 78 patients managed in 14 public hospitals in Hong Kong between the years 2000 and 2010. Patients were identified from the hospital registry using the ICD-10 diagnostic code of the disease. The classification of TA was based on the American College of Rheumatology (ACR) or modified Ichikawa's criteria. Demographic data, clinical presentation, angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The disparity in gender between cohorts of TAK from Asian and European or North American populations has been noted before. About 10–15% of TAK cohorts from Europe or North America comprise males when compared with nearly 20–25% from Asian cohorts of TAK [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Similarly, younger age at diagnosis has been noted for cohorts from Asia than from Europe or North America [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The disparity in gender between cohorts of TAK from Asian and European or North American populations has been noted before. About 10–15% of TAK cohorts from Europe or North America comprise males when compared with nearly 20–25% from Asian cohorts of TAK [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Similarly, younger age at diagnosis has been noted for cohorts from Asia than from Europe or North America [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…About 10–15% of TAK cohorts from Europe or North America comprise males when compared with nearly 20–25% from Asian cohorts of TAK [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Similarly, younger age at diagnosis has been noted for cohorts from Asia than from Europe or North America [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Both cohorts had a similar delay to diagnosis from the first symptom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of this disease is reportedly higher in Asian countries such as Japan (40 per million of population) as compared with Europe or America (ranges from 0.9 to 33 per million of population). [1,2,17]…”
Section: Discussionmentioning
confidence: 99%
“…Regarding situation of TAK in Hong Kong, a study was done involving 78 patients identified over 10 years [17]. The estimated point-prevalence was 1.1 in a million with male to female ratio of roughly 1 to 4.…”
Section: Local Situation In Hong Kongmentioning
confidence: 99%